Making money with words : a guidebook for writers - Hellyer, Clement David (Englewood Cliffs, New Jersey : Prentice-Hall, 1981)
This book is a where-to and a whether-to, whether to become a writer if you aren't one already.
I. A look at the big picture -- II. The creative writing forms -- III. Nonfiction writing forms -- IV. The great miscellany -- V. Non-writing work in the writing world -- VI. Being your own publisher -- VII. The appendices.
Includes bibliographical references (pages 238-254) and index.
Keywords: AUTHORSHIP